2003
DOI: 10.1063/1.1572815
|View full text |Cite
|
Sign up to set email alerts
|

Droplet splashing on a thin liquid film

Abstract: We propose a theory predicting the transition between splashing and deposition for impacting drops. This theory agrees with current experimental observations and is supported by numerical simulations. It assumes that the width of the ejected liquid sheet during impact is precisely controlled by a viscous length lν. Numerous predictions follow this theory and they compare well with recent experiments reported by Thoroddsen [J. Fluid Mech. 451, 373 (2002)].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

26
283
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 345 publications
(311 citation statements)
references
References 25 publications
26
283
2
Order By: Relevance
“…In addition, previous research [47][48][49] has shown that the spread radius r generally obeys the power law r/D ≈ C √ Ut/D at short times after the impact. The sketch of the definition of the spread radius can be found in Ref.…”
Section: Droplet Splashing On a Thin Liquid Filmmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, previous research [47][48][49] has shown that the spread radius r generally obeys the power law r/D ≈ C √ Ut/D at short times after the impact. The sketch of the definition of the spread radius can be found in Ref.…”
Section: Droplet Splashing On a Thin Liquid Filmmentioning
confidence: 99%
“…Actually, splashing can occur at widely different scales, from the astronomical scale when a comet impacts a planet to the microscopic scale in laboratory experiments [47][48][49]. The splashing of droplets on liquid or solid surfaces is a crucial event in a wide variety of phenomena in natural process and industrial applications, such as a raindrop splashing on the ground, the impact of a fuel droplet on the wall of a combustion chamber, and nanoprinting using the laser induced forward transfer technique.…”
Section: Droplet Splashing On a Thin Liquid Filmmentioning
confidence: 99%
“…The industrial applications are manifold including in particular ship slamming, sloshing and granular flows on chutes [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. There is also a huge number of biomedical applications [21][22][23][24][25][26][27][28][29][30][31], while sports applications are such as in skeleton bobsleigh.…”
Section: Introductionmentioning
confidence: 99%
“…While the splash from a lowviscosity liquid develops within a few 10 µs of impact, the splash from a silicone oil develops slowly, becoming evident only after most of the liquid drop has fallen and flattened into a thin pancake [24,25]. We use an axisymmetric Volume-of-Fluid (VOF) code to simulate the impact at reduced ambient pressure [26,27,28]. Our results show that a boundary layer, corresponding to a thin region where the radial flow created by impact adjusts to the no-slip condition at the wall, is created by the impact.…”
mentioning
confidence: 99%